An improved cover cropfallow system for sustainable management of low activity clay soils of the tropics - Tian, G.; Kolawole, G.O.; Salako, F.K.; Kang, B. (1999)
The potential of planted leguminous cover crop fallow as an alternative to the natural regrowth fallow for sustaining the productivity of low activity clay (LAC) soils in the tropics as the fallow period shortens was tested at Ibadan in the forest-savanna zone of southwestern Nigeria. The study, initiated in 1990, compared an improved system (cover crop-fallow) and a traditional system (natural fallow), with the aim of developing an improved cover crop-fallow system for sustainable management of LAC soils of the tropics. Pueraria phaseoloides, an herbaceous, N-fixing, perennial legume with a slow initial growth habit, was selected as a test cover crop. Pueraria was sown with a maize-cassava intercrop at the same season. In a 2-year cycle, 1 year of cropping was followed by 1 year fallow with pueraria for the cover crop-fallow system or with natural regrowth (mainly Chromolaena odorata) for the natural fallow system. Maize-cassava intercropping without a fallow period (continuous cropping) was included as a control. No fertilizer was applied throughout the experimental period. Pueraria produced 253 kg N ha−1 after the fallow period, compared with 109 kg N ha−1 for chromolaena; pueraria was also better in recycling P (11 kg P ha−1) than was chromolaena (9 kg P ha−1). Natural fallow for 1 year increased the maize yield from 75 to 350% from 1992 to 1996, and the cassava yield from 9 to 130% compared with continuous cropping. Cover crop-fallow resulted in a 22 to 72% higher maize yield than the natural fallow from 1992 to 1996. Although in 1992 and 1994 cassava tuber yield was lower with the cover crop-fallow than with the natural fallow, with better pueraria husbandry in 1996, cover crop-fallow increased the cassava tuber yield by 41%. With residue burning, the N balance was 27 kg N ha−1 yr−1 for the pueraria cover crop-fallow system and −15 kg N ha−1 yr−1 for the chromolaena natural fallow system. Cover crop-fallow maintained soil organic carbon status better than the natural fallow. Integration of a pueraria legume cover crop did not affect soil pH. Results indicate cover crop-fallow with pueraria could be a better alternative to traditional natural fallow under shortened fallow periods for raising or maintaining productivity of LAC soils of the humid tropics.